Model Kepemimpinan Partisipatif Vroom-Yetton dalam Meningkatkan Keterlibatan dan Pengambilan Keputusan di Lembaga Pendidikan: Sebuah Kajian Literatur - Asyibli, Basri; Sarmain, Sarmain; Syarifudin, Encep; Lugowi, Rifyal Ahmad (Nusantara: Jurnal Pendidikan Indonesia, 2025)
Purpose – This study aims to explore the application of the Vroom-Yetton Participatory Leadership Model in improving the involvement and effectiveness of decision-making in educational institutions. Because education has a crucial role in producing human resources who can overcome various social problems, and effective leadership in educational institutions is essential to create a productive and innovative learning environment.Method – The method used was a literature review, by collecting and analyzing the literature from various relevant sources, regarding the Vroom-Yetton Model, participatory leadership, and decision-making in an educational context. Includes journal articles and books published between 2015 and 2025, consisting of 18 articles and 3 relevant books. Findings – The study analyzed 21 academic literature that discussed the application of the Vroom-Yetton model in the education sector, with key findings that the application of this model can improve decision quality, decision acceptance rates, and satisfaction with decision-making processes among stakeholders. The Vroom-Yetton model also encourages the development of students' social and leadership skills, as well as creating a more collaborative and responsive learning environment. Research Implications – The implications of this study emphasize the importance of adopting a participatory approach in educational leadership to achieve high-quality learning goals. In addition, this study identifies the need for training for school principals in implementing this model effectively. Further research is needed to explore the application of the model in a broader context in various educational institutions, as well as to identify the factors that influence the successful implementation of this leadership model.